Land use and seasonal effects on water quality and faecal contamination in Batang Layar river, Sarawak, Malaysia - Sabella, Justin; Samuel, Lihan; Jacqleen, Mik; Jongkar, Grinang; Kenneth, Kueh Woon Hou; Lamuel, Lazlus; Thracesy, Munah Assan; Mazzaellynn, Brasenia Umang Thomas; Francis, Senen Alau (Springer Nature, 2026)
Tropical river systems face increasing pollution from anthropogenic activities, yet integrated assessments of land use and seasonal effects on water quality remain limited. This study investigates the impact of land use and seasons on the physicochemical water quality and faecal coliform abundance in the Batang Layar River, Sarawak. Water samples were collected from five sites during the wet and dry seasons. We used a YSI ProDSS Multiparameter for in-situ measurements and performed ex-situ analyses for Faecal Coliform Count (FCC), Total Coliform Count (TCC), and Department of Environment-Water Quality Index (DOE-WQI) parameters. The WQI classified upstream sites (LS1, LS2, LS3) as Class I (Excellent) year-round, while downstream sites (LS4, LS5) shifted from Class II (Very good) in the wet season to Class I in the dry season. Despite the generally favourable WQI scores, wet season FCC concentrations (228.94 to 992.87 CFU/100 mL) exceeded DOE recreational water standards (< 400 CFU/100 mL), particularly near populated areas, due to surface runoff and sediment resuspension. Principal Component Analysis (PCA) identified organic pollution (48.39% variance) and sedimentation (25.75% variance) as dominant factors. Spearman correlation shows strong correlations between FCC, TCC, and organic parameters, confirming shared anthropogenic origins in both seasons. The notable discrepancy between favourable WQI scores and elevated microbial risks highlights the need to integrate bacteriological monitoring into water quality assessments. These findings emphasise the need for integrated water resource management (IWRM) strategies, including improved wastewater infrastructure and riparian buffers implementation, to mitigate seasonal contamination risks and safeguard public and ecosystem health in tropical basins.